"Through the looking glass": present and future tools for writing. Issue 5 (3rd July 2017) - Fernandez, Peter
Abstract : Purpose: Humans use the written language to tell stories and exchange ideas across time and space, and it is the core innovation on which libraries are founded. Design/methodology/approach: Even as the transmission of writing has evolved from hand-written scrolls to mass printing to digital distribution, it has remained one of primary communication methods in the world. Through websites, e-mails, news articles, Facebook posts and more, writing is core to how humans interact. Writing well is also an activity that many people find arduous. Findings: This paper will explore some of the current technologies and emerging trends that are designed to assist with the writing process. Originality/value: Along the way, the paper will highlight some specific applications that can be used now. Examining these technologies, many of which only currently serve niche audiences, serves another purpose as well, as they point the way to what the future of writing will look like.